Understanding the brain connectivity of reward network among youths – a combined fMRI-DTI study - Roslan, Siti Mariam (2024)
Understanding the reward network in youth can shed light on the underlying mechanism that influence important life decisions. Prior studies have pinpointed brain regions activated during reward processing, yet the structural connectivity underlying youth motivation for different rewards is still understudied. This study aims to understand the neural mechanism in different types of reward in the youth population using functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI). Thirty-one right-handed participants (17 males, mean age 23±1) were recruited. Participants performed 2-back tasks in three cue conditions (Cash, Filial, and Certificate) while undergoing fMRI scanning in a 3 Tesla MRI machine, followed by DTI scanning. The accuracy and response time (RT) of the 2-back tasks were recorded and participants were grouped according to their highest score in the three conditions. Random-effects analysis was used to identify brain activations from the fMRI data. Probabilistic tractography was performed on the DTI data. The seeds were reward areas putamen and nucleus accumbens (NAcc), while targets were anterior cingulate cortex (ACC), posterior cingulate cortex (PCC), dorsolateral prefrontal cortex (DLPFC), ventrolateral prefrontal cortex (VLPFC), anterior and posterior insula, and amygdala. The connection probability index (CPI) was calculated from each seed to target. The CPI comparison between groups was analysed for filial and cash groups only using the Mann-Whitney test. Correlation between CPI and reward responsiveness scores (RRS) was analysed using Spearman’s rank correlation coefficient test. Results showed that 15 participants scored highest in Cash condition 16 in Filial condition and 2 in Certificate condition. Significant brain activation was found in the left middle occipital gyrus, which is involved in reward feedback, in conjunction analysis of the three reward conditions. During cash cue, there was significant brain activation in left superior occipital gyrus, known for its role in anticipating and processing monetary reward. Cue filial activated left PCC, which is involved in attention and in viewing personally familiar and loved faces, and left putamen. Both filial and certificate cues activated left angular gyrus, which is involved in reward anticipation. DTI analysis showed that cash group had higher CPI from right putamen to ACC, a decision-making area, compared to filial group. Negative correlation was found between CPI and RRS from left putamen to posterior insula in cash group, possibly due to involvement of posterior insula in loss and punishment processing. Positive correlation was found between CPI and RRS in left NAcc to PCC in filial group. In conclusion, the findings of this study suggest that monetary reward for self holds higher reward value in youth. Furthermore, this study revealed significant role of PCC in filial reward processing.